The development of the cristal multimodal booklet to strengthen students' growth mindset in elementary schools - Esty Yuliana Rabiah Aswadah; Nurul Istiq'faroh; Wahyu Sukartiningsih (Jurnal Inspirasi Pendidikan, 2026)
This study aims to develop a CRISTAL Multimodal Booklet designed to strengthen students’ growth mindset in elementary education. Growth mindset refers to students’ belief that abilities can improve through sustained effort, effective strategies, and constructive feedback. Using a Research and Development (R&D) approach adapted from the ASSURE model, this study focuses on developing and validating the booklet for fifth grade students. The CRISTAL Booklet integrates multimodal elements including text, images, icons, and QR code based digital resources organized into critical reading and interactive speaking activities that support reflective and adaptive learning. The validity of the product was assessed through expert evaluations involving media experts, material experts, and language experts. The results demonstrate that the booklet achieved a “highly valid” category across all aspects, with average scores above 86%, indicating strong alignment with content standards, visual design principles, and linguistic clarity appropriate for elementary learners. These findings confirm that the CRISTAL Multimodal Booklet is a valid instructional product suitable for supporting growth mindset-oriented learning in Indonesian language education.